Effect of major wheat (Triticum aestivum)-based cropping system and long-term residue management practices on soil carbon and nutrient availability in bothplant and soil system in Inceptisol of sub-tropical India - ROY, DEWALI; PURAKAYASTHA, TAPAN JYOTI (The Indian Journal of Agricultural Sciences, 2026)
Residue management has emerged as a critical agronomic strategy for enhancing crop productivity while reducing the environmental footprint of agricultural practices. A long-term field experiment initiated in 2010 at ICAR-Indian Agricultural Research Institute was conducted to evaluate the effects of different cropping systems, viz. maize (Zea mays L.)–wheat (Triticum aestivum L.), pearl millet (Pennisetum glaucum L.)–wheat, and rice (Oryza sativa L.)– wheat; and residue management practices, namely residue incorporation, biochar application, residue burning, and residue removal. Soil organic carbon (SOC), major nutrients availability (N, P and K), and nutrients uptake by grains were assessed during 2022 and 2023. The results indicated that the maize–wheat system consistently outperformed the pearl millet–wheat and rice–wheat systems in terms of soil health and productivity. Among residue management practices, residue incorporation proved most effective, significantly enhancing SOC and improving soil N, P and K availability, which subsequently increased nutrients uptake by grains and overall system productivity. On average, residue incorporation increased total soil nitrogen by 27.4% and grain nitrogen uptake by 35% compared to residue removal. Additionally, a notable 23% improvement in system productivity was observed under residue incorporation relative to no-residue treatments. A strong and significant positive correlation was established between soil available nutrients and grain yield across cropping systems. Overall, the findings highlighted the importance of sustainable residue management practices, particularly residue incorporation and biochar application, in improving soil health, nutrient dynamics, and productivity of intensive cereal-based cropping systems.